2006
DOI: 10.1128/aac.00183-06
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Surgical Wound Infection Model To Determine the Efficacious Dosing Regimen of Retapamulin, a Novel Topical Antibiotic

Abstract: The effect of topically applied retapamulin ointment was evaluated using various dosing regimens in the Staphylococcus aureus and Streptococcus pyogenes wound infection model. Retapamulin (1%, wt/wt) was efficacious using twice-daily (b.i.d.) applications for 4 or 5 days. These data underpinned the decision to evaluate 1% retapamulin b.i.d. in clinical trials.The pleuromutilin retapamulin is a new class of topical antibiotic in development for the treatment of bacterial skin infections caused by Staphylococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
31
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 12 publications
0
31
0
1
Order By: Relevance
“…In this experiment, no antibiotic control was included, which is considered a limitation of this work. However, it has previously been shown that retapamulin and mupirocin ointments reduced the numbers of S. aureus bacteria in this model by 3 to 4 log 10 CFU/ wound following application two or three times per day for 5 to 7 days when the initial infection was comparable to that in this study (approximately 6 log 10 CFU/wound) (21).…”
mentioning
confidence: 63%
See 3 more Smart Citations
“…In this experiment, no antibiotic control was included, which is considered a limitation of this work. However, it has previously been shown that retapamulin and mupirocin ointments reduced the numbers of S. aureus bacteria in this model by 3 to 4 log 10 CFU/ wound following application two or three times per day for 5 to 7 days when the initial infection was comparable to that in this study (approximately 6 log 10 CFU/wound) (21).…”
mentioning
confidence: 63%
“…In this model, a silk suture contaminated with the most common pathogen in SSIs, S. aureus, was implanted into an incision wound on the back of mice and assessment of the infection was performed by counting viable bacteria in the tissue homogenate. The same model has been used previously to assess the effect of systemic and topical antimicrobial agents, and the results observed have been shown to correlate closely with efficacy in clinical trials with human subjects (19)(20)(21). For further details of the experimental model used, see the supplemental material.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…1A) is a selective, prokaryotic protein synthesis inhibitor being developed as a topical antibiotic for treating bacterial infections of the skin. This semisynthetic pleuromutilin has potent in vitro activity against susceptible and multidrug-resistant organisms commonly associated with bacterial skin infections (15,16). Furthermore, in laboratory experiments, retapamulin shows a low propensity for development of resistance, indicating a low likelihood that resistance would develop via target mutation during therapy (9).…”
mentioning
confidence: 99%